Language, sex and power analyzing male-female relations in discourse - Ilustre, Maria Teresa G.; Ramos,Almie Joy A.; Ventura, Eloisa May P. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2004)
This thesis entitled "Language, Sex and Power: Analyzing Male-Female Relations in Discourse" analyzes how power is constructed in the casual conversation between male and female. It aims to re-evaluate the relationship between language and power and to analyze how men and women construct power through language. This research is a descriptive qualitative study using discourse analysis. It will investigate in detail aspects of vocabulary and grammar that are apparent in the casual conversations. In analyzing casual conversations, the researchers will use Norman Fairclough's three levels of Critical Discourse Analysis (CDA) namely: description, interpretation and explanation. The participants in the casual conversations will talk about pre-marital sex and relationship.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.